"Analysis and design of rubber extruder head for automatic production of rubber bend" - JI Tian-chen, PAN Cheng, CUI Xin-yu, TAO Guo-liang (Hecheng xiangjiao gongye)
The process technology of automatic production of rubber bend was introduced. Through theoretical calculation and actual production, the structural parameters of rubber extruder head were designed, including flange model, inner diameter of mouth mold, mandrel diameter, tensile ratio and compression ratio. The length of the main area of rubber extruder head, including shaping zone, compression zone and distributing zone, was analyzed. The results showed that based on the automatic production process of rubber bend, XJ-65 rubber single screw extruder was selected as the production equipment of this process. The flange model of the designed extruder head was DN 80/PN 250, the inner diameter of mouth mold was 77.7 mm, the mandrel diameter was 66.7 mm, the tensile ratio was 0.9, and the compression ratio was 3.1. The length of the shaping zone of the extruder head was designed to be 62 mm, and the length of the compression zone and the distributing zone were both designed to be 120 mm. The flow channel opening amount of the extruder head was designed to be less than 0.05 mm.